PERSEPSI PENGGUNAAN APLIKASI TURNITIN UNTUK MENCEGAH TINDAKAN PLAGIARISME PADA MAHASISWA UNIVERSITAS UDAYANA - Widhiani, Ni Putu Eka Pertiwi; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 2 No 1 (2022), 2022)
The development of increasingly rapid and sophisticated technology is very helpful in facilitating human life, especially in terms of easy access to information. Easy access to information spread on the internet has an impact on students' bad habits. This habit causes students to tend to commit plagiarism. The purpose of this study was to determine how Udayana University students perceive the use of the Turnitin to prevent plagiarism. This study uses a descriptive research method with a quantitative approach with data collection techniques used are questionnaires and literature study. The author uses the Slovin and purposive sampling in this study. The results of this study indicate that the perception of Udayana University students on the use of the Turnitin to prevent plagiarism can be categorized as a positive perception. In general, respondents have understood the benefits of using the Turnitin to minimize cases of plagiarism. Keywords: Perception, Turnitin, Plagiarism, Udayana University